Kerkliedere vir 'n nuwe generasie - 'n Liturgies-himnologiese ontwerp onder voorwaarde van die Ekumene - Kloppers, Elizabeth C. (University of Pretoria, 2013)
Hymns are handed down from generation to generation, from country to country, and from church to church. In every time in history, hymns and songs are needed that are new for that time and generation – hymns through which the timeless message can be voiced in a new and unique way. The historical binding, as well as the ecumenical tie, are thus indispensable features for the church, her liturgy and her music. In the processes of creating new hymns and liturgical forms, the una sancta ecclesia always needs to be in focus. In this study the ecumenical and liturgical movements of the twentieth century, their goals, and the influence they exerted on liturgical renewal and hymn singing, are investigated. The ecumenical meaning of new hymns and liturgical forms is evaluated in terms of these goals. To determine the functionality of new hymns, a theoretical grounding for the various functions of hymns is given. Renewal in the form of contemporary material, new styles and ecumenical-liturgical forms is reflected in the Liedboek van die Kerk (2001), the new hymnal for the Afrikaans-speaking churches. The hymnal is discussed with regard to the content, and the processes of compilation. The versification of the psalms, fundamentalist views, and the resistance to transformation in the processes of canonization, also comes under scrutiny. Documentation, motivation and report of about sixty new hymns and liturgical forms in the Liedboek van die Kerk (2001) are given. Hymns, songs and liturgical forms are researched from hymnological perspectives, by relevant musical and textual analysis, and by exploring their origin, history, working history, and liturgical function. The functionality of the hymns is assessed, and their hymnological, liturgical, contextual and ecumenical significance determined, with regard to the theoretical grounding in the preceding chapters. The conclusion is that ecumenicity is a sine qua non for the hymns and songs of a new generation. History and tradition, but also the contemporary church as a whole, should co-determine processes. The future of liturgical singing depends on the way in which theological, liturgical, hymnological, ecumenical and anthropological fields of tension could be kept in balance. Balance thus needs to be found between functionality, ethics, and aesthetics; between tradition and creativity; historical fidelity and contemporary embodiment; individualism and community; between the individual church and ecumenism; quality and popularity; between Christian/confessional identity, and general religiosity; between orthodox expressions of faith, and the poetical-symbolical shifting of boundaries. Boundaries are exceeded through the singing of hymns – boundaries of language, of confession, of time and space, and boundaries between individuals and groups. Liturgical singing can be the singing of believers of all times and all places only by preserving the traditional ecumenical heritage on the one hand, and on the other hand, through ecumenical cooperation when creating new hymns and forms – thus the one faith in many languages, the audible sign of the una sancta ecclesia. === Thesis (DMus)--University of Pretoria, 2005. === Music === Unrestricted